Changes in Airway Histone Deacetylase2 in Smokers and COPD with Inhaled Corticosteroids: A Randomized Controlled Trial - Sohal, Sukhwinder Singh (Public Library of Science, 2013)
The expression of HDAC2 is reported as reduced in chronic obstructive pulmonary disease (COPD). We assessed HDAC2 expression within the airways of smokers and subjects with COPD and effects of inhaled corticosteroids (ICS), using immuno-histology to contrast with previous molecular methodology. Endobronchial biopsies (ebb) from current smokers with COPD (COPD-CS; n = 15), ex-smokers with COPD (COPD-ES; n = 17), smokers with normal lung function (NS; n = 16) and normal controls (NC; n = 9) were immunostained for HDAC2. A double-blinded, randomized, placebo-controlled 6 months intervention study assessed effects of ICS on HDAC2 in 34 COPD subjects. There was no difference in epithelial HDAC2 staining in all groups. There was a significant reduction in total cell numbers in the lamina propria (LP) in COPD-CS and NS (p<0.05). LP cellularity correlated inversely with smoking history in COPD-CS (R = −0.8, p<0.003). HDAC2 expression increased markedly in NS (p<0.001); in contrast COPD-CS was associated with suppressed signal (p<0.03), while normal in COPD-ES. ICS did not affect HDAC2 cell staining. Our findings suggest that airway HDAC2 expression is increased in the LP by smoking itself, but is reduced in COPD. Ex-smokers have normalised HDAC2 cell expression, but ICS had no effect. The paper emphasise the pit-falls of relying on molecular data alone to define airway changes. Clinical Trial Registration Information: NAME OF REGISTRY: The Australian New Zealand Clinical Trials Registry (ANZCTR) REGISTRY NUMBER: ACTRN12612001111864